"Puffing" in Sarcoscypha austriaca: Back to Ziegenspeck. (3rd March 2020) - Dam, Nico
ABSTRACT: Many discomycetes show the phenomenon of "puffing": the quasi-simultaneous discharge of large numbers of ascospores, rendering them visible to the unaided eye as a whiff of smoke above the fruitbody. Obviously, some kind of synchronization mechanism must be present to make all asci involved burst at about the same time. This mechanism has generally been understood to be of a mechanical nature. For a (small, dung-inhabiting) Ascobolus species, puffing was shown to involve a discharge wave propagating radially outward from a random origin at a speed of about 1.5 cm/s. Using high-speed imaging, we have found no evidence for such a wave in puffing by the (much larger, wood-inhabiting) apothecia of Sarcoscypha austriaca . Rather, extended (but limited) areas seem to become active essentially simultaneously, and within these areas a few percent of the asci discharge their spores randomly. In these large fruitbodies, puffing is found to be preceded by a small but distinct deformation of the apothecium, the geometry of which is such that it increases the lateral compressive stress in the hymenium. The observations suggest that this increase in stress is instrumental in causing many asci to burst quasi-simultaneously in the affected area, a hypothesis essentially already proposed by H. Ziegenspeck, about a century ago.